The Efficiency of Copyright Law in the Digital Space in Kenya: A Case for the Making Available Right in Peer-to-Peer File Sharing (Strathmore Law Review, 2016)
The emergence and use of new technologies such as Peer-to-Peer (P2P) file sharing has brought with it numerous controversies particularly for intellectual property. P2P technologies function by granting its users access to files stored on another P2P user’s hard drive thus enabling them to download on-demand from users who have granted them such access. This aspect of the P2P networks (making files available for download), has been argued to be a violation of the exclusive rights granted by copyright. Consequently, a new right of making available was introduced via the World Intellectual Property Organisation (WIPO) Copyright Treaty (WCT) to supplement the existing copyright regime thus making it more adaptable to the digital age. The lack of ratification of the WCT and the lack of recognition of this right in Kenya, points to an inefficiency of Kenyan copyright laws to prevent P2P sharing of protected works in Kenya.